Answer:
factors of [tex] x^{12}y^{18}+1 = (x^4y^6+1) (x^8y^{12} -x^4y^6 +1)[/tex]
Step-by-step explanation:
We need to find factors of [tex]x^{12}y^{18}+1 can\,\,be\,\, written\,\, as\,\,\\(x^2y^3)^6 + 1\\It\,\, can\,\, be\,\, further\,\, written\,\, as\\((x^2y^3)^2)^3 +1\\Using\,\, the\,\, formula\,\, a^3+b^3 = (a+b)(a^2-ab+b^2)\\Here \,\, a = (x^2y^3)^2 and y = 1\\((x^2y^3)^2)^3 +(1)^3= ((x^2y^3)^2+1) (((x^2y^3)^2)^2 -(x^2y^3)^2 +1)\\= (x^4y^6+1) (x^8y^{12} -x^4y^6 +1)[/tex]
So, factors of [tex] x^{12}y^{18}+1 = (x^4y^6+1) (x^8y^{12} -x^4y^6 +1)[/tex]